Wystawa „Warszawa przyszłości” (1936). Między pokazem architektury a „jarmarkiem dydaktycznym” - Grzegorz Piątek (Miejsce)
The exhibition ”Future Warsaw” opened in 1936 at the Army Museum wing of the National Museum in Warsaw as the first in what was to become a series of exhibitions reflecting on the city, prepared in 1936–1938 by the city hall and related institutions. The press and the public opinion, regardless of the political views, were uniform in their negative assessment of the city’s condition (housing deficit, unhealthy living conditions, lack of greenery, out-dated infrastructure, etc.). At the same time, architects and planners were eager to contribute to the exhibition, seeing it as a long-awaited chance to convey their ideas to a wider public. However, they differed in their approach. Some (including the chief city planner, Stanisław Różański) would prefer to focus on presenting the work of the city hall’s Planning Department. Others, including the architect Edgar Norwerth found this approach too technical, warned that it would turn the show into a ‘didactic fair’ and would rather present proposals for specific neighbourhoods and public spaces. The exhibition was a compromise between these two approaches. The Planning Department presented the daring, CIAM-endorsed regional plan (”Warszawa funkcjonalna”), the general plan, local master plans and examples of good practice in city building, while architects got to show some ambitious projects, including Juliusz Nagórski’s rather utopian proposals for the historic street Nowy Świat (the ‘triple Nowy Świat’) and the exhibition grounds on the right bank of the river. At the same time, the exhibition provided a showcase for a number of institutions linked to the city hall and the authoritarian sanacja regime: the army, the loaning institutions, the Towarzystwo Osiedli Robotniczych (Workers’ Housing Society) or LOT Polish Airlines. The show was met with great interest both from the press and the public (115,000 visitors in two months) and had a pivotal role in creating the image for the mayor Stefan Starzyński as a patron of architecture and a responsible, forward-thinking city father, as well as in raising the profile for the Planning Department and planning in general.